COMPARISON OF GLOBAL MEAN TEMPERATURE SERIES STRATEGIES FOR BEGINERS - Dravid, Pro.Madhuraj Dravid; Rajawat, Pro Mrigkshi (International Journal of Multidisciplinary Research and Studies, 2021)
Studies on the reconstruction of the world mean temperature series are reviewed by introducing three series, Had- CRUT3, NCDC, and GISS thoroughly. Satellite data are used since 1982 in NCDC and GISS series. NCDC series has the foremost complete spatial coverage among the three by using the statistic interpolation technique. The weakened heating in 2000–2009 as revealed in HadCRUT3 data is possibly caused by the shortage of information coverage of this dataset over the Arctic. Three series yielded almost the identical warming trend for 1910–2009 (0.70–0.75 C per 100 years).